2018
DOI: 10.1016/j.ram.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae bacteremia in non-pregnant adult patients at two teaching hospitals

Abstract: Streptococcus agalactiae or group B streptococcus (GBS) is a frequent pathogen in immunocompromised adults. The aim of this study was to determine the relative frequency, clinical presentation, antimicrobial susceptibility profile, and risk factors associated with GBS bacteremia in non-pregnant adult patients. We conducted a retrospective analysis of blood cultures performed in two hospitals between the years 2009-2013. From 1110 bacteremia episodes, 13 were caused by GBS, all of which were susceptible to ampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…The salient features of this case, namely, risk factors specific to GBS bacteremia without focus and risk factors for recurrent disease, are poorly described within the literature. Saad et al 20 reported 13 cases of GBS bacteremia, of which only 5 were without a definitive source in an audit of 1110 cases of bacteremia caused by various organisms. In multivariate analysis, a history of appendectomy (OR, 4.13; 95% CI, 1.37–12.45; P = 0.012) was the only comorbidity significantly different in incidence between GBS bacteremia and bacteremia caused by other organisms groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salient features of this case, namely, risk factors specific to GBS bacteremia without focus and risk factors for recurrent disease, are poorly described within the literature. Saad et al 20 reported 13 cases of GBS bacteremia, of which only 5 were without a definitive source in an audit of 1110 cases of bacteremia caused by various organisms. In multivariate analysis, a history of appendectomy (OR, 4.13; 95% CI, 1.37–12.45; P = 0.012) was the only comorbidity significantly different in incidence between GBS bacteremia and bacteremia caused by other organisms groups.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a review of the literature regarding risk factors pertaining to this presentation, by key word searching “group B streptococcus” in Scopus, CINAHL, Embase, and PubMed. The findings of the retrieved studies are presented in Table 2 1–28 . Group B streptococcal infections (GBSs) in nonpregnant adults have become an increasingly recognized entity.…”
Section: Discussionmentioning
confidence: 99%
“…As group B streptococcal bacteremia is rare in non-pregnant adults, it may occur without apparent focus or with soft tissue infection. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Less commonly, it causes endocarditis, urinary tract infection, and abdominal infections [ 3 - 6 ]. The risk factors for developing invasive S. agalactiae infections include chronic kidney disease, cardiac failure, history of neoplasia, history of ischemic heart disease, and diabetes mellitus [ 5 ]. S. agalactiae endocarditis is an aggressive disease with a significant rate of local and systemic complications [ 6 ].…”
Section: Discussionmentioning
confidence: 99%